Geodesic motion around a supersymmetric $$\hbox {AdS}_5$$ AdS5 black hole - Jens-Christian Drawer; Saskia Grunau (European Physical Journal C: Particles and Fields, 2020)
Abstract In this article the geodesic motion of test particles in the spacetime of a supersymmetric $$\hbox {AdS}_5$$ AdS5 black hole is studied. The equations of motion are derived and solved in terms of the Weierstrass $$\wp $$ ℘ , $$σ $$ σ , and $$ζ $$ ζ functions. Effective potentials and parametric diagrams are used to analyze and characterize timelike, lightlike, and spacelike particle motion and a list of possible orbit types is given. Furthermore, various plots of orbits are presented.